RiceVideo: a web- based platform for good practices - CGIAR Research Program on Rice (2019)
Web-based “RiceVideo” information-education-communication platform (https://video.riceadvice.info) was developed by AfricaRice with focus on videos on good practices for rice cultivation. There have been more than 10,000 views since its release in 2017.